Draft Annual Plan 1978-79 Part III Government of Assam - Planning Commission (Planning Commission, 1977)
The State Government as a matter of policy has decided to cover all the school less villages at least with a primary school on a priority basis. The State Government have identified such school Hess villages. There are 2382 school-less villages with a population of 8.56 laces of people and 1.35 laces children of 6-11 years age group. During 1977-78 697 school- less villages will be covered and it is expected that all the remaining school-less villages covered and it is expected that all the remaining school-less villages will be covered by the next two years of which at .least 500 primary schools will be taken over during 1973-79, by providing teachers out of the one thousand (1000) proposed addl. teachers and building grant from the provision of Rs. 26,00 laces.
Government of Assam
Planning and Development Department
Keywords: General Education; Art and Culture; Medical; Public Health and Sanitation; Sewerage and Water Supply; House sites; Land less laborer; House building loan to Government employees; By Town & Country Planning Department; By Municipal Administration Department; Social Welfare; Other Social and Community Services; Secretariat Economic Services; Employment Motivation Training Programme